MET Measuring energy transition with adhoc statistical tools, Cronbach’s alpha coefficient, Factor Analysis and SCBA method in the Greek Region EMTH - Stathakis, Efthimios; Stampologlou, Metaxenia; kosmidou, Zoe; Gkiourka, Paraskevi; Bandekas, Dimitrios (International Journal of Scientific Research and Management (IJSRM), 2022)
In this work we emphasize the description of the conditions for the application of weighting techniques of the research questionnaire through the Cronbach’s a reliability index but also the Exploratory and Confirmatory analysis of factors to check its structural validity after descriptive statistical analysis. So, this work aims to study the components and factors evolved in the process of energy transition in the region of EMTH, whose economy based on an energy wasteful production system to a sustainable green economy one, with almost zero CO2 emissions. We have used, firstly desk research about the global experience/best practices-bibliography side, and field research done by 128 questionnaires regarding the quantitative and qualitative aspects of transition. The data-components and factors influencing the energy transition-come from 128 interviewed opinion leaders who answered to 64 questions. Data have been used for descriptive/ inferential /statistics, Cronbach’s Alpha Coefficient and Factor Analysis, giving a clear picture about the correlation among environmental, economy, social and managerial factors influencing the transition cost-effectiveness. Additionally, the Social Cost Benefit Analysis(SCBA) tool have been used to document, explore and determine well the compatibility between zero CO2 energy and economic development policies by optimizing the net benefits. The so far efficiency of Greek national and regional electric systems is moderate due to, lack of technological eco-innovations/patents, lack of operational economies of scale, in public and private sectors - small size of service and manufacturing organizations/companies.